An experimental study of solid-filled Bentheim sandstone at seismic frequencies - Lebedev, M.; Mikhaltsevitch, Vassili; Gurevich, B.; Sun, Y.; Glubokovskikh, Stanislav (2019)
© 2018 SEG. The understanding of the dependence of elastic properties of sedimentary rocks on the type of pore filling is of a significant importance for exploration and development of hydrocarbon deposits. In recent years, in connection with increasing attention to the exploration of heavy oil, the study of the effects of solid filling on acoustic properties of porous rocks becomes of high priority. We present the results of the seismic frequency measurements of the elastic properties of Bentheim sandstone with pores filled in sequence with solid (23°C) and liquid (40°C) octadecane. We demonstrate that the results obtained for solid filling are in good agreement with the predictions of the Ciz-Shapiro theory.